The selective electrochemical detection of homocysteine in the presence of glutathione, cysteine, and ascorbic acid using carbon electrodes. - Lee, P; Lowinsohn, D; Compton, R (Royal Society of Chemistry, 2014)
The detection of homocysteine, HCys, was achieved with the use of catechol via 1,4-Michael addition reaction using carbon electrodes: a glassy carbon electrode and a carbon nanotube modified glassy carbon electrode. The selective detection of homocysteine was investigated and achieved in the absence and presence of glutathione, cysteine and ascorbic acid using cyclic voltammetry and square wave voltammetry. A calibration curve of homocysteine detection was determined and the sensitivity is (0.20 ± 0.02) μA μM(-1) and the limit of detection is 660 nM within the linear range. Lastly, commercially available multi walled carbon nanotube screen printed electrodes were applied to the system for selective homocysteine detection. This work presents a potential practical application towards medical applications as it can be highly beneficial towards quality healthcare management.